Reflection on the Crime of Brumadinho-MG and the (Lack Of) Care for the Earth in the Light of Leonardo Boff (Revista Iberoamericana de Bioética, 2023)
This study aims to discuss the (lack of) care for the Earth in the crime of Brumadinho-MG, from the perspective of Leonardo Boff. It is a theoretical reflection based on the thinking of Leonardo Boff, in which his contributions to values such as collective responsibility, compassion, cooperation, solidarity, respect and care for the Earth are discussed. The reflection focuses on the corporate crime that occurred in the municipality of Brumadinho-MG when the B1 Dam of the Córrego do Feijão mine burst. It also focuses on the negligence and inaction of the company responsible, whose interests were overwhelmingly economic. This crime has had irreparable consequences for the environment and human lives and serves as a critique for society on the importance of reformulating the paradigm of coexistence, by raising bioethical issues that involve protecting and caring for the Earth.
Keywords: protection bioethics; environmental disasters; environmental bioethics